STRATEGI KOMUNIKASI PEMASARAN PT. BALI MEDIA GRAFIKA DALAM MENINGKATKAN BRAND AWARENESS KORAN TRIBUN BALI DI KALANGAN MASYARAKAT BALI - Eggy Eriska, Ni Made; Sugiarica Joni, I Dewa Ayu; Pradipta, Ade Devia (E-Jurnal Medium; Vol 2 No 02 (2018), 2018)
ABSTRA CT   Bali Media Grafika is a print media company in Bali with its newspaper product called Harian Pagi Tribun Bali. Tribun Bali Newspaper is a new newspaper that has been present in Bali since 2014. Tribun Bali is incorporated in the Tribun Network which is a group of newspapers owned by Kompas Gramedia. The purposel of this researcha is to find out the marketing communication strategy used by PT. Bali Media Graphic in increasing brand awareness of Bali Tribune newspaper among Balinese people. Thisr study usesa a descriptive qualitative approach. The technique of determining informants in this study uses purposive and snowball techniques (snowball techniques). Data is obtained through observation, in-depth interviews, and documentation. The author uses interactive model data analysis techniques, Milles and Huberman through several stages, that is data collection, data reduction, data presentation, and conclusion drawing and verification. The results of this study indicate the marketing communication strategy used by PT. Bali Media Graphic in increasing brand awareness Tribun Bali newspaper that is applying the concept of marketing mix (marketing mix) with 4P elements, that is: product, place, price, promotion, and using 8 elements of the promotion mix. The eight elements are: advertising (Advertising), direct marketing (direct marketing), interactivep marketing (interactive) / internet amarketing, sales promotion, publicity or public relations, personal selling (personal selling) , event (event), word of mouth marketing (Word of Mouth).   Keywords: Marketing communication strategy, Brand Awareness, Tribun Bali Newspaper, PT. Bali Media Grafika, Marketing Mix, Promotion Mix